Analisis SWOT Tim Hockey Outdoor Putra Sumatera Utara pada PON XXI 2024 Aceh-Sumut: Penelitian - Nanda Ibnasia Rahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Aim of this study to analyze the SWOT of the North Sumatera Men's Outdoor Hockey Team for the XXI PON 2024 Aceh-North Sumatera. The research method used is descriptive with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The data analysis techniques involve data reduction, data presentation, and drawing conclusions. The results of this study are as follow: Strengths were identified from the team’s high dedication and independence, support from various parties, adoption of international-level training programs, and training schedule that include try ins and try outs. Weaknesses were identified from as a lack of facilities and infrastructure, insufficient financial appreciation, limited competitive experience, and human resource quality. Opportunities were identified from factors competition regulation, bonuses, and the advantages of being the host. Threats were identified from the pressure of the gold medal target, delays in financial support, the risk of injuries and mental health issues among athletes, and negative influences from the media.